Bacterial Contaminations of Broiler Chicken Meat Marketed in Banjarbaru - Herliani Herliani; Muhammad Ilmi Hidayat (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2020)
This research aims to find out how high the level of bacterial contamination found in broiler chicken meat sold at the Bauntung Market, Banjarbaru. The method used in this research is the sampling method to determine the sample using the random sampling method used to determine the experimental test sample. This sampling was carried out for three days at 8:00 AM and 11:00 PM. The variables observed in this study were physical observation, the number of bacteria (TPC), and the type of bacteria. The data obtained were then performed a t-test (paired samples test) using a variety of SPSS (Statistical Product and Service Solution) program analysis 18. Laboratory analysis was carried out in the Microbiology Laboratory of the Faculty of Agriculture, Lambung Mangkurat University. The results obtained indicate that there are significant differences in Sig. (2-tailed) (<0.05) between the collection times of the number of bacteria, so it can be concluded that the average level of bacterial contamination at the time of collection at 07.00 am lower than at 10:00 noon. Which is 2.13 x 109 cfu / g and 5.81 x 109 cfu / g. The whole sample taken at 07.00 am did not exceed the threshold, while taken at 10:00 noon had exceeded the threshold required by SNI. Bacterial contaminants that grow on EMBA and SSA media include Escherichia coli, Klebsiella sp., Citrobacter, Shigella sp., Salmonella sp., and Providencia.